Codification and Progressive Development of the International Treaty Law (the Vienna Convention 40th Anniversary) - O. N. Кhlestov (Московский журнал международного права)
The Vienna conference, during which there had been elaborated Convention on the law of the treaties, took place 40 years ago. The article demonstrates the significance of this Convention, describes history of its elaboration. The main goal of the Conference was to create such norms, which could enhance the development of the treaty relations between states, assist in concluding treaties on a fair basis without use of force. Stability of international relations primarily depends on the stability of international treaties.Vienna convention codified existing norms on the law of the treaties. Several new norms had also been included into it thus reflecting the practice of states and tendencies of the development of the international law. In the article new principles and norms on the law of the treaties which emerged as a result of the conference are analyzed, among them:treaties are void if had been concluded under duress: treaties are void if they contradict jus cogens norms; In the article new norms and principles, which were introduced by the Vienna Convention of 1969, are also analyzed: reservations to international treaties, termination of international treaties, Also in the article is described the discussion about the right of state formations, which are parts of federate states, to conclude treaties.In the conclusion it is stressed that Vienna Convention of 1969 is an important step in the progressive development of international law. It facilitated the development and refinement of national legislation on the issue of international treaties in many countries, including the USSR and the Russian Federation.